Between Amnesia and Anamnesis: Re-Membering the Fractures of Colonial History - Anne Donadey (Studies in 20th & 21st Century Literature, 1999)
The Greek word "anamnesis," a term used by several contributors to this section, means "remembrance," or going back (in time) through memory…
Keywords: anamnesis; Colonial History; remembrance; memory; amnesia